2021
DOI: 10.3390/medicina57030298
|View full text |Cite
|
Sign up to set email alerts
|

Use of Public Automated External Defibrillators in Out-of-Hospital Cardiac Arrest in Poland

Abstract: Background and objectives: National medical records indicate that approximately 350,000–700,000 people die each year from sudden cardiac arrest. The guidelines of the European Resuscitation Council (ERC) and the International Liaison Committee on Resuscitation (ILCOR) indicate that in addition to resuscitation, it is important—in the case of so-called defibrillation rhythms—to perform defibrillation as quickly as possible. The aim of this study was to assess the use of public automated external defibrillators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Still, in only a minority of the 22 cases in which AED use was indicated it was applied by Maccabi clinic personnel (8, 36.4%), though chest compression CPR was provided to all cardiac arrest victims. Earlier AED applications may have further improved outcome by allowing defibrillation (when indicated) at an earlier stage and prior to EMS arrival [ 26 ]. The findings in our healthcare provider survey showed that most respondents had undergone AEDs training (89.4%), most within the last three years (67.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Still, in only a minority of the 22 cases in which AED use was indicated it was applied by Maccabi clinic personnel (8, 36.4%), though chest compression CPR was provided to all cardiac arrest victims. Earlier AED applications may have further improved outcome by allowing defibrillation (when indicated) at an earlier stage and prior to EMS arrival [ 26 ]. The findings in our healthcare provider survey showed that most respondents had undergone AEDs training (89.4%), most within the last three years (67.9%).…”
Section: Discussionmentioning
confidence: 99%
“…If the day is divided into two stages: daytime 8:00-20:00 and nighttime 20:00-8:00, then the ratio of daytime and nighttime is 70-30%. [33] Denmark.…”
Section: Experiences and Conclusion Of Some Countriesmentioning
confidence: 99%
“…People around them will avoid the whole family, and the victims can only leave their homes, families, and jobs. Therefore, psychological nursing should be done patiently during systemic treatment [19,20].…”
Section: Lightning Injure Treatmentmentioning
confidence: 99%